Numerical and experimental investigation of single phase flow characteristics in stirred tanks using Rushton turbine and flotation impeller. (November 2015) - Basavarajappa, Manjunath; Draper, Teri; Toth, Pal; Ring, Terry A.; Miskovic, Sanja
Graphical abstract: Highlights: Numerical and experimental (PIV measurements) investigation of single phase flows using flotation impeller. Effect of impeller size, off-bottom clearance, Reynolds number on mean flow behavior. Radial flow generated at intermediate clearance with sharp gradient in velocity components in axial direction. Flow transition from radial to axial-type flow observed experimentally and correctly predicted by CFD. Flow transition coupled with considerable drop in power number – typical mixed/axial flow impellers values. Abstract: In this study, computational fluid dynamics (CFD) simulations are used to investigate turbulent single phase flow characteristics in lab-scale stirred tanks with different geometric variations. Water at standard conditions is used as operating fluid. Rushton turbine ( RT ) and flotation impeller ( FI ) are used to agitate the fluid leading to turbulent flows in the tank. For FI, impeller diameter, d, is varied and three sizes corresponding to d values of 75, 100, and 150 mm are considered. Additionally, for 75 and 100 mm FI, off-bottom clearance, C, is varied from 100 ( D / 3 ) to 60 mm ( D / 5 ). The impeller based Reynolds number, Re, ranged from 29, 000 to 120, 000. CFD results are compared with LDA data from the literature for RT and in-house PIV data for FI . CFD predictions for FI are found to match experimental measurements satisfactorily with accurate prediction of flow transition at lower C . The normalized flow properties are observed to be invariant with Re for both impellers in fully turbulent regime. Mean flow characteristics for FI suggests that the flow is characterized by strong radial and tangential velocities close to impeller with peak values along disc level. Turbulence kinetic energy profiles close to impeller are characterized by two peaks suggesting development of trailing vortex which is further verified using swirling strength visualization. For FI with diameter equal to 100 mm, flow transition in which mean flow changes from radial flow (double loop) to axial-type (single loop) flow is observed when C is reduced. Both PIV measurements and CFD simulation are able to predict this transition accurately. Using both torque on rotating parts and volume averaged dissipation rate of turbulence kinetic energy, power numbers are calculated for both impellers. The axial-type flow at smaller clearance is marked by significant drop in power number value.